Common Infectious Diseases Among the Hospitalized Elderly Patients - Mansooreh Momen Heravi; Hasan Afzali; Zahra Soleimani; Moin Matin (Sālmand, 2011)
Objectives: The elderly are more susceptible to the infectious diseaseswith higher risk of morbidity and mortality. Variouspresentations of infectious disease in the elderly can lead to delay in diagnosis. This study aimed to evaluate the clinical featuresof infectious diseases and laboratory findings among the hospitalized elderly patients.